2017
DOI: 10.2174/1381612822666161230142931
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation: A Novel Therapeutic Target/Direction in Atherosclerosis

Abstract: Over the past two decades, the viewpoint of atherosclerosis has been replaced gradually by a lipiddriven, chronic, low-grade inflammatory disease of the arterial wall. Current treatment of atherosclerosis is focused on limiting its risk factors, such as hyperlipidemia or hypertension. However, treatment targeting the inflammatory nature of atherosclerosis is still very limited and deserves further attention to fight atherosclerosis successfully. Here, we review the current development of inflammation and ather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 188 publications
(206 reference statements)
1
93
0
12
Order By: Relevance
“…The pathophysiology of AVS can be divided in two phases: An initiation phase and a propagation phase. The initiation phase of AVS precedes calcification and is similar to the pathophysiology of atherosclerosis [32][33][34][35][36]. In the aortic valve, the initiation phase is ignited by damage to the upper cell layer of the valve comprising of valvular endothelial cells (VEC), a process caused by mechanical, oxidative, or shear stress [37].…”
Section: Pathophysiology Of Lp(a)-induced Avsmentioning
confidence: 99%
“…The pathophysiology of AVS can be divided in two phases: An initiation phase and a propagation phase. The initiation phase of AVS precedes calcification and is similar to the pathophysiology of atherosclerosis [32][33][34][35][36]. In the aortic valve, the initiation phase is ignited by damage to the upper cell layer of the valve comprising of valvular endothelial cells (VEC), a process caused by mechanical, oxidative, or shear stress [37].…”
Section: Pathophysiology Of Lp(a)-induced Avsmentioning
confidence: 99%
“…Most of these biological processes and pathways enriched in the BD gene signature overlap with those responsible for the development of atherosclerosis [43,44]. This suggests that the association between BD and cardiovascular diseases may have some genetic basis rather than shared environmental risk factors or side effects of psychotropic medications.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis occurs secondary to endothelial dysfunction that permits the retention of oxidized low‐density lipoprotein (LDL) in subendothelial space, which then induces the infiltration of immune cells and production of chemokines in endothelial cells (Weber & Noels, ). Anti‐inflammatory pathway‐associated therapeutic approaches have been suggested to improve the prognosis of AS patients who have received an optimal standard of care (Li, Li, Li, & Zhou, ). Circulating oxidized LDL, which is associated with the inflammatory variables of AS, plays a major role in the development of AS (Li et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Anti‐inflammatory pathway‐associated therapeutic approaches have been suggested to improve the prognosis of AS patients who have received an optimal standard of care (Li, Li, Li, & Zhou, ). Circulating oxidized LDL, which is associated with the inflammatory variables of AS, plays a major role in the development of AS (Li et al., ). It was also suggested that the judicious use of biomarkers and genetic information would reduce the risk of AS (Libby, Bornfeldt, & Tall, ).…”
Section: Introductionmentioning
confidence: 99%